The Character Education Through Analogy Learning Implementation on Vector Concepts - Safitri, Islamiani; Hasibuan, Lily Rohanita (Jurnal Penelitian & Pengembangan Pendidikan Fisika, 2018)
The problem of this study is the acts of the criminal increase in North Sumatra, so it needs the characters’ building begin from school. Besides, the teacher of physics should be able to instill character values through analogy learning about the concept of physics. This study aims to determine the results of physical knowledge and student responses after applying analogy learning to instill character values. The subjects of this study were X-IPA 1 students of SMA Negeri 1 Rantau Utara. This research is descriptive qualitative with two stages, namely the preparation stage (referring to the development that uses the 4-D model namely Defines, Design, Develop, and Disseminate) and the implementation stage. While the instruments used in this study are observation sheets on the implementation of RPP, student response questionnaires, and tests of knowledge competency results. The conclusions of this study are there is an increase in the results of students’ physics knowledge competencies and a positive response to the implementation of analogy learning in instilling character education through the concepts of physics taught.